2015
DOI: 10.1007/s10806-015-9559-6
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Trust and Credibility in a Continuously Evolving Organic Food System

Abstract: Credibility is particularly important in organic food systems because there are only marginal visual and sensorial differences between organic and conventionally produced products, requiring consumers to trust in producers' quality claims. In this article I explore what challenges the credibility of organic food systems and I explore how credibility of organic food systems can be maintained, using the Danish organic food system as a case study. The question is increasingly relevant as the sale of organic food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
0
27
0
4
Order By: Relevance
“…Besides, there are many situations in which quality claims are weakened due to producers breaking the law [18]. For these reasons, dialogue with consumers to sustain trust can be more important than specific information about traceability or production techniques [72]. In support of this statement, Pole and Gray (2012) [71] (p. 96) found that members of a CSA in New York considered the relationship with the farmer to be an essential aspect of CSA.…”
Section: Challenges and Potential Improvementsmentioning
confidence: 99%
“…Besides, there are many situations in which quality claims are weakened due to producers breaking the law [18]. For these reasons, dialogue with consumers to sustain trust can be more important than specific information about traceability or production techniques [72]. In support of this statement, Pole and Gray (2012) [71] (p. 96) found that members of a CSA in New York considered the relationship with the farmer to be an essential aspect of CSA.…”
Section: Challenges and Potential Improvementsmentioning
confidence: 99%
“…Trust sangat erat kaitannya dengan bagaimana individu berhubungan dengan risiko dan ketidakpastian. Untuk mendapatkan sebuah kepercayaan atau trust, maka seseorang butuh memiliki kredibilitas (atau dapat dipercaya yang secara harfiah layak dipercaya), karena kredibilitas merupakan persepsi dari individu lainnya (Thorsøe, 2015). Pada sejumlah penelitian tersebut terbukti bahwa credibility memainkan peran penting dan memberikan pengaruh positif terhadap perceived ease of use, dan perceived usefulness (Baogoza dan Ozer, 2012).…”
Section: Pendahuluanunclassified
“…Pengembangan diagram jalur dalam penelitian ini berupaya menguji pengaruh kredibillitas, kepercayaan, risk, internet use terhadap kegunaan yang dirasakan (perceived usefulness), kemudahan penggunaan (perceived ease of use), dan pada akhirnya pengaruh pada niat responden dalam melakukan transaksi ulang melalui e-commerce mobile platform. (Thorsøe, 2015).…”
Section: Metode Penelitianunclassified
“…Network-building strategies. Building trust and reciprocity are two main strategies, or mechanisms, through which individuals construct social networks (Lyon 2000;Portès 1998;Pretty and Ward 2001 Trust lubricates cooperation and association by reducing transaction costs between people (Fukuyama 1995) and by lowering the odds of betrayal among individuals with incomplete knowledge of one another (Thorsøe 2015). In doing so, it also reduces the complexity of situations and influences decision-making processes.…”
Section: The Concept Of Social Capitalmentioning
confidence: 99%
“…In doing so, it also reduces the complexity of situations and influences decision-making processes. Trust can be inherited (e.g., through family, kinship) or accrue through marriage, frequency of contact, establishment of a long-standing relationship, reputation, openness, consistency, credibility, and so on (Fisher 2013;Thorsøe 2015). Reciprocity involves a short-or long-term exchange of goods or services between individuals, balanced over time.…”
Section: The Concept Of Social Capitalmentioning
confidence: 99%